Increased TGFβ1 and SMAD3 Contribute to Age-Related Aortic Valve Calcification - Chakrabarti, Mrinmay; Bhattacharya, Aniket; Gebere, Mengistu G.; Johnson, John; Ayub, Zeeshan A.; Chatzistamou, Ioulia; Vyavahare, Narendra R.; Azhar, Mohamad (Frontiers in Cardiovascular Medicine, 2022)
Aims Calcific aortic valve disease (CAVD) is a progressive heart disease that is particularly prevalent in elderly patients. The current treatment of CAVD is surgical valve replacement, but this is not a permanent solution, and it is very challenging for elderly patients. Thus, a pharmacological intervention for CAVD may be beneficial. In this study, we intended to rescue aortic valve (AV) calcification through inhibition of TGFβ1 and SMAD3 signaling pathways. Methods and Results The klotho gene, which was discovered as an aging-suppressor gene, has been observed to play a crucial role in AV calcification. The klotho knockout (Kl–/–) mice have shorter life span (8–12 weeks) and develop severe AV calcification. Here, we showed that increased TGFβ1 and TGFβ-dependent SMAD3 signaling were associated with AV calcification in Kl–/– mice. Next, we generated Tgfb1- and Smad3-haploinsufficient Kl–/– mice to determine the contribution of TGFβ1 and SMAD3 to the AV calcification in Kl–/– mice. The histological and morphometric evaluation suggested a significant reduction of AV calcification in Kl–/–; Tgfb1± mice compared to Kl–/– mice. Smad3 heterozygous deletion was observed to be more potent in reducing AV calcification in Kl–/– mice compared to the Kl–/–; Tgfb1± mice. We observed significant inhibition of Tgfb1, Pai1, Bmp2, Alk2, Spp1, and Runx2 mRNA expression in Kl–/–; Tgfb1± and Kl–/–; Smad3± mice compared to Kl–/– mice. Western blot analysis confirmed that the inhibition of TGFβ canonical and non-canonical signaling pathways were associated with the rescue of AV calcification of both Kl–/–; Tgfb1± and Kl–/–; Smad3± mice. Conclusion Overall, inhibition of the TGFβ1-dependent SMAD3 signaling pathway significantly blocks the development of AV calcification in Kl–/– mice. This information is useful in understanding the signaling mechanisms involved in CAVD.